Fitoquímica, atividade antiviral e antioxidante de "Distictella elongata (Vahl) Urb. (Bignoniaceae)" - Leandro Ribeiro Simoes (2010)
Some plant metabolites have been found to have potential therapeuticapplications against different genetically and functionally several viruses. Their mechanisms of action are diverse and, often, multiple. The relevance of reactive oxygen and nitrogen species in viral diseases has already been described. Distictella elongata (Vahl) Urb is a vegetal specie of Bignoniaceae family. Ethanolic extracts of leaves andstems from Distictella elongata were, in vitro, evaluated for their antiviral activity by MTT assay. Two models of DNA viruses were used: HSV-1 and VACV-WR, and one model of RNA virus: EMC. The leaves ethanolic extract presented anti-HSV-1 activity (EC50 = 142.8 ± 5.3 g/mL) while the stems ethanolic extract did not present any activity in the tested concentrations (EC50 > 500 g/mL). The chromatographic fractionation of the leaves extract provided nine fractions. The fractions that were eluted with EtOAc and EtOAc:MeOH presented antiviral activity: anti-HSV-1(EC50 = 164.4 ± 5.7 g/mL) and anti-EMC (EC50 = 36.6 ± 1.2 g/mL) for the first and anti-HSV-1 (EC50 = 147.6 ± 3.3 g/mL) for the second. The directed bioassay left to isolation by chromatographic techniques of pectolinarin of the EtOAc:MeOH fraction, in addition to mixtures of terpenoids ursolic acid, oleanolic acid and pomolic acid and the steroid -sistosterolpresent in EtOAc fraction. The pectolinarin showed anti-HSV-1 (EC50 = 314.5 ± 22.7 g/mL) and anti-VACV-WR (EC50 = 207.1 ± 9.6 g/mL) activities. The terpenoids oleanolic acid and ursolic acid had activity against HSV-1, EC50 = 3.8 ± 0.6 g/mL and 6.2 ± 0.1 g/mL, respectively, but also elevated citotoxicity: CC50 = 4.2 ± 0.8 g/mL for oleanolic acid and CC50 = 8.1 ± 0.9 g/mL for ursolic acid. The leaves extract (EAC50 =28.03 ± 0.46 g/mL) and the fraction EtOAc:MeOH (EAC50 = 58.00 ± 0.89 g/mL) presented antioxidant activity by DPPH assay, but the EtOAc fraction did not present that. The phytochemical study of leaves extract of D. elongata demonstrated that terpenoids and phenols, especially heterosidic flavonoids such as pectolinarin, were responsible by its antiviral activity. Add to that the second class of substances confers toit the free radicals scavenging capacity. Therefore these results suggest a possible utilization of plant special metabolites such as alternatives to actual antiviral pharmacotherapeutic. Key words: Distictella elongata, Bignoniaceae, antiviral, antioxidant, HSV-1, VACV-WR,EMC, DPPH.